Assessment of government’s involvement in implementation of national policy on early childhood education in Nigeria - Akinrimisi, Ayomiposi Rebecca; Adeyemi, Babatunde Adeniyi; Iroegbu, Victoria Ihekerenma (Universitas Ahmad Dahlan, 2020)
The study examined the areas of Government’s involvement as stated in the national policy on early childhood education in South western Nigeria. It determined the implementation processes of the national policy on ECE on the areas of Government’s involvement and also investigated the level of compliance in the implementation processes of the national policy on ECE and the stakeholders' assessment of Government’s involvement in the implementation of the national policy on ECE. The study adopted descriptive survey research design. Data was collected from 72 head teachers, 144 classroom teachers and 144 parents of early childhood education pupils as well as 30 State Ministry of Education officials. Multistage sampling procedure was used to select the sample for the study. Three instruments were used for this study. The results of the study showed that governments were involved in the regulation of the establishment and registration of pre-school facilities at 91.7% and 96.7%, development and implementing educational support services to orphans and vulnerable children at 51.4% and 90%. The study concluded that Government’s involvement in the implementation of the national policy on early childhood education is only to a little extent. All the implementation processes of the national policy on education were not followed by the government.